Methylene blue--an endocrine modulator - Haluzík, M; Nedvídková, J; Schreiber, V (Sbornik lekarsky, 1995)
Methylene blue (MB) is a thiazine dye used in the treatment of methemoglobinemia. It may represent a new class of anti-oxidant drugs which competitively inhibit the reduction of molecular oxygen to superoxide by acting as an alternative electron acceptor for tissue oxidases. Because of its strong free radicals scavenging effect MB was experimentally used in the treatment of reperfusion syndrome. MB is soluble guanylate cyclase inhibitor. It was found to inhibit the stimulation of soluble guanylate cyclase by nitric oxide and vasodilatators. Another effect of MB is inhibition of prostacyclin synthesis by endothelial cells and isolated arteries independently of its effects on cGMP accumulation. We investigated the MB in series of experimental endocrine situations in which its free radicals scavenging effect could play a role. We observed that MB partly inhibited the increase in adenohypophyseal weight, cAMP and blood prolactin levels in male rats after the administration of estrogens. MB also blocked the increase of another free radicals scavenger-the metalloenzyme ceruloplasmin in the blood of estrogenized rats and prevented the increase of bone mineral after estradiol treatment. MB produced a decrease in adenohypophyseal ascorbic acid content. The blood thyroxine levels increased and the anterior pituitary TSH concentration decreased after MB treatment.
Keywords: thyroxin; methylenová modř; Rats; AMP cyklický; adenohypofýza; Animals; Thyrotropin; Methylene Blue; krysa rodu Rattus; thyreotropin; mužské pohlaví; Estradiol; Male; Pituitary Gland, Anterior; Thyroxine; zvířata; Cyclic AMP; estradiol